Identification of Biomarkers for Systemic Distribution of Nanovesicles From Lactobacillus johnsonii N6.2 - Harrison, Natalie A.; Gardner, Christopher L.; da Silva, Danilo R.; Gonzalez, Claudio F.; Lorca, Graciela L. (Frontiers in Immunology, 2021)
The ability of bacterial extracellular vesicles (EV) to transport biological molecules has increased the research to determine their potential as therapeutic agents. In this study, Lactobacillus johnsonii N6.2-derived nanovesicles (NV) were characterized to identify components that may serve as biomarkers in host-microbe interactions. Comparative proteomic and lipidomic analyses of L. johnsonii N6.2 NV and cell membrane (CM) were performed. The lipidomic profiles indicated that both fractions contained similar lipids, however, significant differences were observed in several classes. LC-MS/MS proteomic analysis indicated that NV contained several unique and differentially expressed proteins when compared to the CM. Analysis of Gene Ontology (GO) terms, based on cellular component, showed significant enrichment of proteins in the cytoplasm/intracellular space category for the NV fraction. Based on these results, the proteins T285_RS00825 (named Sdp), Eno3 and LexA were selected for studies of localization and as potential biomarkers for host-microbe interactions. Immunogold staining, followed by scanning and transmission electron microscopy (SEM and TEM, respectively), revealed that Sdp was preferentially localized along the cell wall/membrane, and on NV-like structures surrounding the bacteria. These results were confirmed using immunofluorescence staining in Caco-2 cells incubated with NV. Consequently, we evaluated the potential for NV surface-exposed proteins to generate an immune response in the host. Plasma from individuals administered L. johnsonii N6.2 showed that IgA and IgG antibodies were generated against NV and Sdp domains in vivo. Altogether, these results show that L. johnsonii N6.2 NV have the potential to mediate host interactions through immune modulation.